Iron-based bulk metallic glasses. (1st April 2013) - Suryanarayana, C; Inoue, A
<x xml:space="preserve">Abstract</x> The current status of research and development in Fe-based bulk metallic glasses (BMGs) is reviewed. Bulk metallic glasses are relatively new materials possessing a glassy structure and large section thickness. These materials have an exciting combination of properties such as high mechanical strength, good thermal stability, large supercooled liquid region and potential for easy forming. Ever since the first synthesis of an Fe-based BMG in an Fe-Al-Ga-P-C-B system in 1995, there has been intense activity on the synthesis and characterisation of Fe-based BMGs. These BMGs exhibit some unique characteristics which have not been obtained in conventional Fe-based crystalline alloys. This uniqueness has led to practical uses of these bulk glassy alloys as soft magnetic and structural materials. This review presents the recent results on the glass-forming ability, structure, thermal stability, mechanical properties, corrosion behaviour, soft magnetic properties and applications of Fe-based bulk glassy alloys developed during the last 15 years. This review also highlights the advanced analysis of their properties which has contributed significantly to the progress in understanding and developing of the Fe-based BMGs. The future prospects of Fe-based BMGs have also been presented.